Factors affecting savings and investment decisions of Malaysian youth - Ang, Ean Ting; Koo, Siew Xuan; Leong, Kai Ni; Phang, Zi Wei; Yap, Chien Jeen (2022)
The objective of this study is to explore the factors affecting the savings and investment decisions of Malaysian Youth. Furthermore, the four independent variables, which are financial literacy, peer influence, parental socialization and locus of control, have been chosen to see whether they are associated with the savings and investment decisions, which is the dependent variable. In this study, 386 copies of the Google Form survey were distributed to Malaysian Youth. IBM SPSS Statistics 26 was used to analyze and interpret the data collected from the Google Form survey. The data were analyzed using descriptive analysis and inferential analysis. The results of this study showed that savings and investment decisions were affected by financial literacy, peer influence, parental socialization and locus of control. Last but not least, limitations and recommendations for future research were discussed in later chapters.